The Concept of Qiwāmah in the Perspective of Feminist Activists Amina Wadud and Zainab al-Ghazali - Aqidatul Islamiyah; A. Faizul Mubin; Zubeir Mohamad Nur Sholeh (مجلة النور الدولية للقرآن والحديث, 2024)
The debate on the leadership roles of men and women (qiwāmah) in Islam is often associated with different interpretations of religious texts. This article aims to uncover and compare the concept of "qiwāmah" through the interpretation of Surah al-Nisa': 34 from the perspective of two female feminist figures, Amina Wadud and Zainab al-Ghazalī, who have different backgrounds. The qualitative comparative method is used in this research, using library research techniques for data collection. This study analyzes data related to their interpretations and views of the Quranic text through their various works, identifying similarities and differences in the interpretation of the Quran. The findings of this study show that there are different interpretations of the meaning of "qiwāmah". Wadud argues that "qiwāmah" signifies relative leadership based on "capability", where anyone capable, regardless of gender, is entitled to lead others. In contrast, Zainab views leadership based on "responsibility", where men are providers for women, reflecting an equal role between the two. In conclusion, both scholars support gender justice and equality, rejecting the notion that the concept of leadership in the Quran is reserved for men due to physical or rational creation factors, and thus opposing domination where the strong can oppress the weak.